2020
DOI: 10.1039/d0ra00541j
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitored photocatalytic activity and electrochemical performance of an rGO/Pt nanocomposite synthesizedviaa green approach

Abstract: Herein, we have reported the real-time photodegradation of methylene blue, an organic pollutant, in the presence of sunlight at an ambient temperature using a platinum-decorated reduced graphene oxide (rGO/Pt) nanocomposite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The peak of C 1s at 287.08 eV is attributed to C=O, confirming the presence of GO in all samples. The fact that this peak moved to 289.08 at 30% of calcium shows that graphene oxide was converted to rGO [48]. The Auger Cu LMM triplet of Cu2O was detected at binding energies between 570 and 721 eV [49].…”
Section: Resultsmentioning
confidence: 96%
“…The peak of C 1s at 287.08 eV is attributed to C=O, confirming the presence of GO in all samples. The fact that this peak moved to 289.08 at 30% of calcium shows that graphene oxide was converted to rGO [48]. The Auger Cu LMM triplet of Cu2O was detected at binding energies between 570 and 721 eV [49].…”
Section: Resultsmentioning
confidence: 96%
“…They all display obvious D bands and G bands originating from carbon sp 2 domains and structural defects [ 60 ]. The G band is attributed to the E 2g mode of C sp 2 atoms and the D band arises due to the A 1g symmetry [ 61 ]. The structural disorder of a graphitic structure could be estimated according to the I D /I G .…”
Section: Resultsmentioning
confidence: 99%
“…A higher degree of graphitization is beneficial to promote the overall conductivity of the final product and enhance the electrochemical activity. In addition, the crystallinity of the 2D band (about 2700 cm −1 ) in PtNiCo/rGO 200 is higher, which is predicted to be more corrosion resistant in DMFC [ 61 ]. The wide 2D band shows the multilayer structure of rGO, affirming the existence of graphene and mainly coming from a double resonance process that links phonons to the electronic band structure [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the increase of Pt precursor concentration will lead to a highly efficient photocatalytic rate, implying that the Pt could induce a better electron transfer property with higher current and conductivity as compared to the pure RGO. Based on the TEM images (Kasturi et al, 2020;Neppolian et al, 2012), a well uniform and good distribution of Pt nanoparticles with an average size of 2.5 nm on the surface of rGO can be observed, suggesting that no agglomeration of Pt nanocluster was formed. Owing to the remarkable high electron transfer property, the optimized photocatalyst (20 wt% Pt precursor) exhibited a remarkable photocatalytic activity and degraded 98% of methylene blue in the presence of sunlight at an ambient temperature under 180 minutes.…”
Section: Graphene-based Nanomaterials For Co 2 Adsorptionmentioning
confidence: 97%
“…Besides using TiO 2 as cocatalyst, some researchers incorporated Pt ions on GO via a cheap reducing agent to form RGO/Pt nanocomposites. Kasturi et al (2020) have reported honey as a reducing agent which plays a role in the in situ functionalization of the Pt ions on the surface of RGO via a reduction method (Kasturi et al, 2020). Interestingly, the increase of Pt precursor concentration will lead to a highly efficient photocatalytic rate, implying that the Pt could induce a better electron transfer property with higher current and conductivity as compared to the pure RGO.…”
Section: Graphene-based Nanomaterials For Co 2 Adsorptionmentioning
confidence: 99%